Transition-Metal-Catalyzed Allylic Substitution Reactions: Stereoselective Construction of α- and β-Substituted Carbonyl Compounds - Oliver, Samuel; Evans, P. Andrew (Synthesis, 2013)
The stereoselective synthesis of α- and β-substituted carbonyl compounds remains a significant area of interest in organic chemistry. This is largely due to their ubiquity and versatility as synthetic intermediates and the importance of this functionality in a range of biologically important agents. In this context, the transition-metal-catalyzed allylic substitution provides an extremely powerful tool for the asymmetric construction of a variety of α- and β-tertiary and quaternary substituted carbonyl compounds. This review highlights pertinent historical developments of these reactions, from the seminal work with enolate equivalents to the more recent developments with unstabilized enolates and acyl anions. It also outlines the most important mechanistic aspects of these transformations in order to provide insight into the current scope and limitations and potential areas for further development.1 Introduction2 Unstabilized Enolate Nucleophiles2.1 Enolate Equivalents2.1.1 Enamines2.1.2 Imines2.1.3 Silyl Enol Ethers2.1.4 Enolstannanes2.1.5 Decarboxylative Approaches2.2 Metal Enolates2.2.1 Boron Enolates2.2.2 Tin Enolates2.2.3 Copper Enolates2.2.4 Zinc Enolates2.2.5 Magnesium Enolates2.2.6 Sodium Enolates2.2.7 Lithium Enolates3 Acyl Anion Equivalents3.1 Acylmetal Nucleophiles3.2 ‘Masked’ Acyl Anion Equivalents4 Conclusions
Keywords: acyl anion; allylic substitution; asymmetric catalysis; enamine; enolate; metal-catalyzed; silyl enol ethers